2018
DOI: 10.14740/jcs366w
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathologic Study of Various Breast Lesions by Fine Needle Aspiration Cytology (FNAC)

Abstract: Background: The expected and significant role of cytological diagnosis is to distinguish benign from malignant processes. Fine needle aspiration cytology (FNAC) of the breast has two main goals. One is to confirm a radiological and clinical benign lesion and avoid unnecessary surgery and the other is to confirm a malignant diagnosis and allow definite treatment planning. Methods: In breast lesions, rapid diagnosis by aspiration cytology can be particularly useful for allaying the apprehension and anxiety of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
4
2
1
Order By: Relevance
“…In the present study, malignant lesions were common in the age group 20-34 years, followed by 35-49 years, findings that differ from other studies [ 9 , 13 , 25 ]. According to Bukhari, women in their 4 th , 5 th , and 6 th decades of life were the most affected with ductal carcinoma [ 12 ] while Bhatnagar et al .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, malignant lesions were common in the age group 20-34 years, followed by 35-49 years, findings that differ from other studies [ 9 , 13 , 25 ]. According to Bukhari, women in their 4 th , 5 th , and 6 th decades of life were the most affected with ductal carcinoma [ 12 ] while Bhatnagar et al .…”
Section: Discussioncontrasting
confidence: 99%
“…Globally, FNAC has been used to guide the diagnosis and follow-up of patients on treatment for breast cancer [ 11 , 12 ]. It can be of use in advanced carcinoma or in patients not willing to undergo surgery [ 13 ]. Generally, this may form the basis of management in such cases.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the mean age of presentation was significantly higher for patients with malignancies than for those with benign lesions. This finding is similar to that of other studies performed by Rioki et al (16), Madan et al (15), Embaye et al (13) and Khanam et al (1), as they also reported the maximum incidence of cases in younger (<30 years) age group. However, the study by Singh and Tyagi (17) reported that patients aged 31 to 40 years had the most cases of breast lumps.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the present study revealed that fibroadenoma was the most common diagnosis followed by inflammatory lesion/mastitis/abscess among the benign lesions of the breast. These findings are in agreement with those of other studies performed by Singh and Tyagi, Rioki et al (16), Madan et al (15), Qadri et al (14), Embaye et al (13) and Khanam et al (1). These authors also reported that the most common diagnosis was fibroadenoma in benign lesions (1,(13)(14)(15)(16)(17).…”
Section: Discussionsupporting
confidence: 91%
“…In this study of 75 cases, 25(33.3%) were malignant, and50 (66.7%) were benign. Otherstudies showed 50 breast masses on FNAC and found that 7 cases (14%) were malignant and (86%) were benign 15 .Similaritystudied 757 cases on FNAC and found that most cases were benign (50.2%), followed by malignant cases(31.4%) 16 . The percentage of benign cases in our study was closer to that in Bangladesh 15 .…”
Section: Discussionmentioning
confidence: 81%